Informação científica em ciências ambientas : circulação de fontes acadêmicas entre os agentes-produtores-usuários na universidade - Santos, Maria do Carmo Menezes dos (2019)
[Introduction] Contemporary societies depend largely on the products of scientific activity. The circulation of academic sources of scientific information, which occurred among agentsproducers- users at the university, through teaching and research, is crucial in defining agendas and interests that guide the production of new knowledge and the training of future generations of researchers. [Premise] In Brazil, environmental sciences develop under different epistemological influences. [Objective of the research] In this Thesis, we seek to characterize the circulation of academic sources of scientific information in environmental sciences, produced in the Doctoral Programs of the Full Network Association of Graduate Studies in Development and Environment. [Object of research] In this regard, the usage, the remission and the recurrence to works-authors and themes-contents are analyzed, based on the knowledge production of academic researchers in environmental sciences. The empirical field of this research was the Doctoral Programs of the Full Network Association of Graduate Studies in Development and Environment. [Method] The research approach adopted was methodological interdisciplinary. Bibliographic and documentary research were used as methodological tools. [Research procedures] The data survey was organized into three different periods, spread over decades: (a) 1960-1970; (b) 1980-1990; (c) 2000-2018. For empirical analysis, the study was concentrated in the period between 2013-2018, considering the defenses of thesis carried out in the Doctoral Programs of the Full Network Association of Graduate Studies in Development and Environment. The main categories of research analysis were divided into two axes: (a) traditions of usage of works-authors / themes-contents; (b) innovations in the use of works-authors / themes-contents. The heuristic part of the research turned to the processes of usage, redemption and recurrence of works-authors / themescontents in the knowledge produced, and in circulation, in environmental sciences. [Research results] The results obtained point to a formal inconsistency in the circularity of academic sources of scientific information, so that the use of theoretical-conceptual tradition in the production of knowledge in environmental sciences at the analyzed empirical field were not consolidated. [Conclusion] It was concluded that the circulation of academic sources of scientific information in environmental sciences in the Doctoral Programs of the Full Network Association of Graduate Studies in Development and Environment does not yet presents or have characteristics oriented towards the consolidation of design in regard of theoretical traditions of the field of environmental sciences. In addition to producing with limited, theoretical or conceptual remission in this area of knowledge, given the local or regional circulation of the academic sources found and analyzed, it does not present scope and expansion, highlighting, above all, usage, remission, decontextualized and generalized recurrence of scientific information at the university.